Epidemiological and economic consequences of lumpy skin disease outbreaks on farm households in Khyber Pakhtunkhwa, Pakistan - Saqib, Shahab E.; Yaseen, Muhammad; Visetnoi, Supawan; Sikandar,; Ali, Shoukat (Frontiers in Veterinary Science, 2023)
The livestock sector plays a crucial role in sustaining the livelihoods of millions of families across the world, especially in developing countries. However, farming households that rely on agriculture and livestock are particularly susceptible to the impacts of various infectious diseases and natural disasters. This study focuses on estimating the economic burden imposed on households by lumpy skin disease (LSD) in Pakistan and explores the effect of various socioeconomic factors on mortality ratio. Data were collected through a questionnaire survey from 406 farmers and were analyzed through descriptive statistics to calculate the monetary losses. In addition, the study employed fractional probit regression to identify factors affecting mortality ratio. The results demonstrate significant economic impacts of LSD on farm households in Pakistan, leading to direct and indirect losses and reduced milk productivity. Exotic cows were found to be more susceptible to mortality compared to indigenous cows. The study also found that farmers' education, experience, household income per month, vaccination, domestic-commercial, commercial animals, and access to information were negatively associated with mortality. The findings of this study emphasize the need for preventative measures such as affordable vaccines, treatment, and improved livestock health and welfare to mitigate the negative effects of LSD on farmers' income and the local economy.